Pola Asuh Orang Tua Dalam Membentuk Kedisiplinan Belajar Siswa Kelas VIII-C di MTsN 2 Trenggalek - Ulfa Dwi Wulandari; Bagus Setiawan (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
The family is an institution that has responsibility for providing education. The family is a core component in forming a child's character. Families generally consist of two important elements, namely father and mother. Every family definitely has its own way of providing care to children. Thus, the character formed in children will also vary, especially in the aspect of learning discipline. The aim of this research is to describe the form of parenting patterns applied by parents in forming learning discipline for students in class VIII-C MTsN 2 Trenggalek and to describe the factors underlying parenting patterns in an effort to form learning discipline for students in class VIII-C MTsN 2 Trenggalek. The method used by researchers is a qualitative-descriptive research method with data collection techniques in the form of observation, interviews and documentation. The results of this research show that there are three forms of parenting patterns applied by parents in forming learning discipline for students in class VIII-C MTsN 2 Trenggalek, namely authoritarian, democratic and permissive parenting patterns. Furthermore, the factors that influence parenting patterns in shaping the learning discipline of class VIII-C students at MTsN 2 Trenggalek include ideology, geographical location and ethical, religious, economic and lifestyle norms. Keywords: , ,